2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6696848
|View full text |Cite
|
Sign up to set email alerts
|

First analysis and experiments in aerial manipulation using fully actuated redundant robot arm

Abstract: In this paper we describe a system for aerial manipulation composed of a helicopter platform and a fully actuated seven Degree of Freedom (DoF) redundant industrial robotic arm. We present the first analysis of such kind of systems and show that the dynamic coupling between helicopter and arm can generate diverging oscillations with very slow frequency which we called phase circles. Based on the presented analysis, we propose a control approach for the whole system. The partial decoupling between helicopter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 10 publications
(15 reference statements)
0
91
0
Order By: Relevance
“…The tasks range from automatic vision based landing to aerial manipulation using a fully actuated robotic arm mounted on a helicopter [3], [4], [5], [6], [7].…”
Section: Existing Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks range from automatic vision based landing to aerial manipulation using a fully actuated robotic arm mounted on a helicopter [3], [4], [5], [6], [7].…”
Section: Existing Systemmentioning
confidence: 99%
“…On the same plate as the FC, the power supply unit (3) is mounted. The last tray holds the primary data link modem (4), two servo control units (5) and the foldable antenna of the primary data link (7 ). The bottom of the box has a slit shaped opening to allow the antenna to fold in during landing or for placing the box on a desk during developing.…”
Section: Avionics Boxmentioning
confidence: 99%
“…DLR aerial manipulating robot in Huber et al (2013), composed of an autonomous helicopter and a 7-DOF industrial manipulator, is able to grasp a straight pole on the ground and the research studied the movement of centre of gravity when grasping. In University of Pennsylvania (Mellinger et al, 2011), their research focused on the estimation and control for aerial grasping and manipulation with quadrotor.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of research groups have put their efforts and recent contributions include interesting lightweight manipulator designs and model-free or model-based control methods such as those in Jiang and Voyles (2013), Parra-Vega et al (2013), Gioioso et al (2014), Orsag et al (2013Orsag et al ( , 2014, , Bellens et al (2012), Fumagalli et al (2014), Huber et al (2013), Mellinger et al (2011Mellinger et al ( , 2013, Marconi and Naldi (2012), Marconi et al (2011), Srikanth et al (2011, Pounds et al (2011), Papachristos and Tzes (2013), Sreenath and Kumar (2013), Montserrat Manubens et al (2013), Manubens et al (2013). Based on these and other relevant efforts, it has been shown that an aerial robot, although a floating manipulating base, has the capacity to ensure stable physical interaction and a variety of tasks including grasping or position-controlled force tracking can be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these and other relevant efforts, it has been shown that an aerial robot, although a floating manipulating base, has the capacity to ensure stable physical interaction and a variety of tasks including grasping or position-controlled force tracking can be conducted. These tasks have been assisted by intelligent manipulator design such as the deltarobot in Fumagalli et al (2014), the redundant robotic arm in Huber et al (2013) or the grasping hand in Pounds et al (2011). On a different direction, physical interaction by means of rigid contact mechanisms has also been investigated in several works such as (Bellens et al 2012;Marconi et al 2011;Darivianakis et al 2014).…”
Section: Introductionmentioning
confidence: 99%